SELECTIVE SEX ABORTION - A REAL WAR AGAINST WOMEN - POOJA BAHUGUNA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Carl Sandburg is credited with the idea that everyone in the world should continue to see each newborn child as a gift from God. In a patriarchal society, female feticide is the deliberate killing of female fetuses. The slaughter of female fetuses’ is referred to by this word. Women face prejudice in all countries where men rule, and it is unlawful for women to bear children in some of these societies. It was previously difficult to detect the direction of the embryo while it was still in the mother's womb. If the newborn girl turned out to be a girl, she would be given opium-laced milk before being put to sleep. This procedure is no longer employed since contemporary technology has advanced to the point where it can replace it. Female feticide is primarily caused by the prevalence of female genital mutilation, while other factors will be discussed in greater depth later in the paper. Dowries are the responsibility of the women whose daughters are marrying. Daughters are viewed as a social and economic burden, in contrast to men, who are expected to perform rituals for the souls of their deceased parents and grandparents while also providing stability for their family as they age. Sons are said to be capable of performing rituals for their departed parents and ancestors. Although abortion is legal in India, it is illegal to terminate a woman's pregnancy only because the fetus she is carrying is female. Lawbreakers are liable to harsh penalties. The laws are strictly enforced. Nonetheless, a growing number of illegal actions continue to be committed in defiance of these rules. This essay will look into the socio-legal quandary created by the widespread practice of female feticide in India, as well as the consequences of women's exclusion from Indian society